Selection of four types arbuscular mycorrhizal fungi in oil palm seedling planted in histosol soil - Maria Viva RINI; Radix SUHARJO; Lestari WIBOWO; David IRVANTO; Adhy ARIYANTO (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2021)
Arbuscular mycorrhizal fungi (AMF) are beneficial microbes for plants, especially in the absorption of nutrients and water from the soil. Some factors that influence the effectiveness of this fungus are the suitability of the AMF species with their host plants and abiotic condition such as soil characteristics. Therefore, this study aims to determine the type of AMF that produced the best growth and nutrient uptake in oil palm seedlings planting in histosol soil. This study used a single factor treatment design consisting of 9 AMF treatments, namely control without AMF (T1), given Glomus sp. (T2), Gigaspora sp. (T3), Entrophospora sp. (T4), Acaulospora sp. (T5), a mixture of Glomus sp. and Gigaspora sp. (T6), a mixture of Glomus sp. and Entrophospora sp. (T7), a mixture of Gigaspora sp. and Entrophospora sp. (T8), and a mixture of Glomus sp., Gigaspora sp., Entrophospora sp., and Acaulospora sp. (T9). Each treatment was repeated five times. The experimental design used was a randomized block design. In the AMF treatment, 500 spores per seedling were given when the seedlings were transplanted from prenursery to the main nursery. The seedlings were kept in the prenursery for 3.5 months and in the main nursery for nine months. The results showed that the type of mycorrhizal that consistently produced better seedling growth and nutrients uptake compared to the control were Glomus sp. (T2) and a mixture of Gigaspora sp. and Entrophospora sp. (T8), which supported by data on plant height, number of leaves, shoot dry weight, and total nutrient uptake of N, P, K, Ca, Mg, and B.